A CNL protein in wild emmer wheat confers powdery mildew resistance. Issue 3 (22nd July 2020) - Li, Miaomiao; Dong, Lingli; Li, Beibei; Wang, Zhengzhong; Xie, Jingzhong; Qiu, Dan; Li, Yahui; Shi, Wenqi; Yang, Lijun; Wu, Qiuhong; Chen, Yongxing; Lu, Ping; et al.
Summary: Powdery mildew, a fungal disease caused by Blumeria graminis f. sp. tritici ( Bgt ), has a serious impact on wheat production. Loss of resistance in cultivars prompts a continuing search for new sources of resistance. Wild emmer wheat ( Triticum turgidum ssp. dicoccoides, WEW), the progenitor of both modern tetraploid and hexaploid wheats, harbors many powdery mildew resistance genes. We report here the positional cloning and functional characterization of Pm41, a powdery mildew resistance gene derived from WEW, which encodes a coiled‐coil, nucleotide‐binding site and leucine‐rich repeat protein (CNL). Mutagenesis and stable genetic transformation confirmed the function of Pm41 against Bgt infection in wheat. We demonstrated that Pm41 was present at a very low frequency (1.81%) only in southern WEW populations. It was absent in other WEW populations, domesticated emmer, durum, and common wheat, suggesting that the ancestral Pm41 was restricted to its place of origin and was not incorporated into domesticated wheat. Our findings emphasize the importance of conservation and exploitation of the primary WEW gene pool, as a valuable resource for discovery of resistance genes for improvement of modern wheat cultivars.